Nongrowing season methane emissions–a significant component of annual emissions across northern ecosystems. (25th April 2018) - Treat, Claire C.; Bloom, A. Anthony; Marushchak, Maija E.
Abstract: Wetlands are the single largest natural source of atmospheric methane (CH4 ), a greenhouse gas, and occur extensively in the northern hemisphere. Large discrepancies remain between "bottom‐up" and "top‐down" estimates of northern CH4 emissions. To explore whether these discrepancies are due to poor representation of nongrowing season CH4 emissions, we synthesized nongrowing season and annual CH4 flux measurements from temperate, boreal, and tundra wetlands and uplands. Median nongrowing season wetland emissions ranged from 0.9 g/m 2 in bogs to 5.2 g/m 2 in marshes and were dependent on moisture, vegetation, and permafrost. Annual wetland emissions ranged from 0.9 g m −2 year −1 in tundra bogs to 78 g m −2 year −1 in temperate marshes. Uplands varied from CH4 sinks to CH4 sources with a median annual flux of 0.0 ± 0.2 g m −2 year −1 . The measured fraction of annual CH4 emissions during the nongrowing season (observed: 13% to 47%) was significantly larger than that was predicted by two process‐based model ensembles, especially between 40° and 60°N (modeled: 4% to 17%). Constraining the model ensembles with the measured nongrowing fraction increased total nongrowing season and annual CH4 emissions. Using this constraint, the modeled nongrowing season wetland CH4 flux from >40° north was 6.1 ± 1.5 Tg/year, three times greater than the nongrowing season emissions of the unconstrained model ensemble. The annual wetland CH4 flux was 37 ± 7 Tg/year from the data‐constrained model ensemble, 25% larger than the unconstrained ensemble. Considering nongrowing season processes is critical for accurately estimating CH4 emissions from high‐latitude ecosystems, and necessary for constraining the role of wetland emissions in a warming climate. Abstract : The extensive wetlands in temperate, boreal, and tundra regions emit varying amounts of methane, a potent greenhouse gas, during the warmer growing season as well as the colder nongrowing season, but the importance of nongrowing season emissions is not well understood. Using existing data from 191 sites, we find that nongrowing season fluxes were significantly greater than zero and amounted to 10%–50% of annual emissions, depending on which ecosystem type and biome. Comparing observations and process‐based methane models indicated that nongrowing season emissions were under‐estimated by process‐based models; using a measurement‐informed model constraint leads to 25% larger annual methane emissions from northern latitudes.